Consumer Decision-Making Styles in the Digital Product Category - Sunčana Piri Rajh (Tržište, 2022)
Purpose – The aim of this paper is to explore consumer decision-making styles when buying digital products, and to identify different clusters of consumers based on their approaches in choosing digital products. The literature regarding consumer decision-making styles when purchasing digital products is rather scarce. Therefore, a research study on behavioral patterns and product attributes important to consumers when they purchase digital goods might contribute to a more comprehensive understanding of this type of consumer behavior while also broadening the existing body of knowledge. Design/Methodology/Approach – Empirical data were collected using an online questionnaire consisting of items borrowed from the relevant literature and adapted to the research context. Research results are presented using descriptive statistics, exploratory factor analysis, Cronbach’s alpha coefficient, and k-means cluster analysis. Findings and implications – This study has revealed four distinct consumer groups that differ in their consumer decision-making styles when buying digital products. Both theoretical and managerial implications of the research findings are discussed. Results of this research serve as helpful insights into consumer behavior characteristics in a digital products market, providing digital goods companies with valuable inputs for planning their marketing strategies and activities. Limitations – The results of the present research apply to digital products in general. Future research should develop and confirm these initial findings further by incorporating specific digital product categories and focusing on other socio-cultural contexts. Originality – By identifying six consumer decision-making styles and four distinct clusters, this study contributes to a more comprehensive understanding of consumer approaches when buying digital products, thereby broadening the existing theoretical knowledge of consumer decision-making styles.